Government Performance Analysis Through Health Services for Low Income Mindle Track Kartu Indonesia Sehat (KIS) in South Binjai District - Harahap, Aisyah Winanda; Azriana, Alya; Tarigan, Asmaria Naomi; Liana, Devi; Irawan (Proceedings of The International Conference on Computer Science, Engineering, Social Science, and Multi-Disciplinary Studies, 2025)
Government performance in delivering public services has long been a central concern, particularly in the health sector, which directly affects people’s well-being. Within the framework of Program Jaminan Kesehatan Nasional (JKN), providing accessible and high-quality healthcare services for Kartu Indonesia Sehat (KIS) holders serves as an important indicator of the effectiveness of government social policies. This study aims to analyze government performance in providing healthcare services to low-income KIS beneficiaries in South Binjai District. A descriptive qualitative approach is employed to explore social realities in depth. Primary data are gathered through open-ended questionnaires distributed to low-income KIS users. The collected data are analyzed to yield empirical insights into community experiences, perceptions, and evaluations of the healthcare service quality they received.